Anti-SARS-CoV-2 Antibody Levels in Chronic Kidney Disease Stage 5 Patients on Maintenance Haemodialysis: A Prospective Observational Study from a Government Hospital in Central Kerala, India - Biju K Gopinath; Zainab Yaseen; Arun Karat; Usha Samuel (Journal of Clinical and Diagnostic Research)
Introduction: The Coronavirus Disease-2019 (COVID-19) pandemic caused significant mortality among vulnerable populations in India, including patients with Chronic Kidney Disease (CKD) on maintenance haemodialysis. The vaccination was the mainstay of prevention. CKD Stage 5 patients requiring haemodialysis have high mortality and poor immune response to many infections, including postvaccination Hepatitis B and Influenza. Antibody response to COVID-19 vaccination in these patients was lower compared to the general population. Aim: To estimate Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) IgG antibody level in the blood sample of CKD Stage 5 maintenance haemodialysis patients. Materials and Methods: A prospective observational study was conducted at the Nephrology department of Government Medical College, Ernakulam, Kerala, India for six months. A total of 55 patients of CKD Stage 5 who were on maintenance haemodialysis were included in the study. The control group consisted of 55 matched close relatives of patients. The anti-SARS-CoV-2 antibody levels were measured in both groups. Blood samples for antibody testing were drawn from the cases, along with routine monthly tests done before a dialysis session. The blood samples were collected simultaneously from the controls, sent to the hospital’s central laboratory and processed on the same day. Serum was separated after centrifugation and then stored in small 1 mL Eppendorf tubes/vials and refrigerated at 2-8°C. These serum samples were analysed for anti-SARS-CoV-2 IgG antibody levels in both cases and controls within 24 hours, using the Chemiluminescence Immunoassay (CLIA) method on the VITROS ECiQ Immunodiagnostic system. Relevant data were collected in MS Excel and statistical analysis was done using Statistical Package for the Social Sciences (SPSS) software version 27.0. An unpaired t-test was applied for comparison, with a p-value <0.05 considered statistically significant. Results: Males predominated in the test/case group (43, 78.1%), while females were more prevalent in the control group (42, 76.4%). The comparison of antibody levels between cases and controls showed higher levels in the control group, with a p-value of 0.65, indicating a lack of significance (p-value >0.05). Interestingly, participants vaccinated with Covishield had significantly higher antibody levels at 188.95 BAU/mL compared to those vaccinated with Covaxin or other vaccines, with a p-value of 0.04. Conclusion: The antibody response in CKD Stage 5 haemodialysis patients was found to be lower compared to the control group; however, the difference was not significant. In the current study, the antibody response to the Covishield vaccine was high compared to other vaccine. Larger sample size studies should be conducted in future to validate the results of the present study, if similar COVID-19 like situation reoccurs.